Synthesis of organ pipe sound based on simplified physical models - A. CZYŻEWSKI; B. KOSTEK; S. ZIELIŃSKI (Archives of Acoustics, 2014)
Problems related to the implementation of a physical model based synthesis of an organ pipe sound are discussed. A new approach to the physial modelling of an organ pipe sound, namely the waveguide synthesis is introduced. The results of some experiments with this kind of synthesis are presented. Specific features of presented methods and corresponding applications are quoted. Examples of a computer analysis of both synthesized and real musical sounds are presented and compared.